(untitled) - Stadlerova, Hana; Taylor, Daniela; Tomanova, Milena (Aura musica, 2019)
Music and Art are integrated into the educational area of Art and Culture as compulsory subjects, so they should integrate fully in the development of the child. In practice, we can see that they are still underestimated, the contents of some lessons are even in direct contradiction to the framework given by the National Curriculum. It is necessary to educate pedagogues to be aware of the irreplaceable role of art education, which enables pupils not only to acquire new knowledge and skills, but also to express emotions and subjective views of the world. In the context of the reality of Music and Art, activities were offered, which were first verified in the framework of didactic preparation. Their progress and outputs can become an inspiration for schools with practical innovation.
Keywords: Art Education; National Curriculum; competencies; educational area Arts and Culture; interdisciplinary; Music; Art; project; innovation